Combination therapy of fenofibrate and ursodeoxycholic acid in patients with primary biliary cirrhosis who respond incompletely to UDCA monotherapy: a meta-analysis - Zhang Y; Li S; He L; Wang F; Chen K; Li J; Liu T; Zheng Y; Wang J; Lu W; Zhou Y; Yin Q; et al. (Dove Medical Press, 2015)
Yan Zhang,1,2,* Sainan Li,1,* Lei He,1 Fan Wang,1 Kan Chen,1 Jingjing Li,1 Tong Liu,1 Yuanyuan Zheng,1 Jianrong Wang,1,3 Wenxia Lu,1,3 Yuqing Zhou,1,4 Qin Yin,1,4 Yujing Xia,1 Yingqun Zhou,1 Jie Lu,1 Chuanyong Guo1 1Department of Gastroenterology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, 2Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, 3The First Clinical Medical College of Nanjing Medical University, Nanjing, 4The First Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China *These authors contributed equally to this work Background: Although the effectiveness of treatment with ursodeoxycholic acid (UDCA) and fenofibrate for primary biliary cirrhosis (PBC) has been suggested by small trials, a systematic review to summarize the evidence has not yet been carried out.Methods: A meta-analysis of all long-term randomized controlled trials comparing the combination of UDCA and fenofibrate with UDCA monotherapy was performed via electronic searches.Results: Six trials, which included 84 patients, were assessed. Combination therapy with UDCA and fenofibrate was more effective than UDCA monotherapy in improving alkaline phosphatase (mean difference [MD]: -90.44 IU/L; 95% confidence interval [CI]: -119.95 to -60.92; P<0.00001), gamma-glutamyl transferase (MD: -61.58 IU/L; 95% CI: -122.80 to -0.35; P=0.05), immunoglobulin M (MD: -38.45 mg/dL; 95% CI: -64.38 to -12.51; P=0.004), and triglycerides (MD: -0.41 mg/dL; 95% CI: -0.82 to -0.01; P=0.05). However, their effects on pruritus (odds ratio [OR]: 0.39; 95% CI: 0.09–1.78; P=0.23), total bilirubin (MD: -0.05 mg/dL; 95% CI: -0.21 to 0.12; P=0.58), and alanine aminotransferase (MD: -3.31 IU/L; 95% CI: -14.60 to 7.97; P=0.56) did not differ significantly. This meta-analysis revealed no significant differences in the incidence of adverse events (OR: 0.21; 95% CI: 0.03–1.25; P=0.09) between patients treated with combination therapy and those treated with monotherapy.Conclusion: In this meta-analysis, combination therapy with UDCA and fenofibrate was more effective in reducing alkaline phosphatase than UDCA monotherapy, but it did not improve clinical symptoms. There did not appear to be an increase in adverse events with combination therapy. Keywords: randomized controlled trials, combination therapy, monotherapy, fibrates, odds ratio, risk difference